Impact of ChatGPT’s Conversational Features on EFL Learners’ English-Speaking Proficiency in Latin America: A Literature Review - Mora Preciado, Franklin Absalon; Molina Pinargote, Frelly María (Arandu UTIC, 2025)
This article aims to shed light on how the conversation features of ChatGPT can help improve and reach an independent English-speaking level according to the guidelines of the Common European Framework of Reference on English for the Languages as a Foreign Language learners in Latin America. The methodology in this study was conducted by searching academic databases, such as, Redalyc, Scopus, Scielo, and Google Scholar, then searched using keywords such as: “ChatGPT”, “English as a Foreign Language speaking skills”, “English language learning”, and “Latin America”. Additionally, articles published between the years 2024 and 2025 were selected to support this review. Furthermore, this research indicates how the conversation features of ChatGPT can benefit students and teachers by using ChatGPT as a supplementary tool in overpopulated classrooms. Also, one significant attribute of ChatGPT is that it can maintain a human-like conversation in any of the six levels of English. Moreover, this article reflects on how factors that hinders the English-speaking learning can be overcome. Finally, an ethical recommendation is given in the appropriate use of ChatGPT or any AI tool.